Acceptable Noise Levels Determined by Traditional and Self-Assessed Methods - Barnett, Megan; Jones, Alisha L.; Westbrook, Erin (Journal of the American Academy of Audiology, 2021)
Background Many apps have been developed for users to screen their hearing in their own home. The purpose of this study was to investigate the validity and efficiency of a self-assessed acceptable noise level (ANL) in comparison to the traditional ANL measurements.Research Design A within-subject repeated measures research design was utilized.Data Collection and Analysis Sixty-two adults with normal hearing were recruited from Auburn University and the surrounding community. ANLs were measured utilizing the traditional measurement as well as the self-assessed ANL via the Unitron uHear app.Results Within-subject repeated measures of variance revealed no significant differences between traditional ANL measurements and self-assessed ANL measurements. Significant differences were found for time required for testing in each condition, revealing self-assessed testing to be significantly faster.Conclusion The self-assessed ANL measurement via the Unitron uHear app is a valid and efficient measurement of ANL in adults with normal hearing.
Keywords: hearing aids; assistive listening devices; acceptable noise levels